The Association and Relation of ABO Blood Group with the Breast Cancer in Kirkuk Governorate - Zaki , Sahar Mohammed; Hasan, Fatehiya Fathullah; Saydoka, Kmaran Mahmud; Amin, Nyaz Amed (Diyala Journal of Medicine, 2019)
Background: Cancer is common; it is the second most common cause of death in the Western worlds, Breast cancer accounts for around 20-25% of all female cancers in both India and UK world. There are differences between the percentages of patients with various malignant tumors in our country and those in the Western world. ABO blood groups are a stable feature of a population and they differ among various socioeconomic, geographical and ethnic groups and many risk factors are associated with the development of breast cancer. It is mentioned that bloods type has an influence on susceptibility and outcomes Objectives: The aims of this study are: To found any association between breast cancer and ABO blood group. To know what is the frequency of each blood group in relation to patients with breast cancer. Materials and patients: This study has been carried in Azady teaching hospital in Kirkuk on 250 patients with breast cancer and classified according to their blood group. The control sample was 300 healthy donors from Kirkuk blood bank and classified according to their ABO group and frequency of each sample estimated statistically and compared with each other. Results: This study shows the distribution ABO blood groups among patients with breast cancer were as follow: blood group type (A) 64% (160) , blood group type (O) 18% (45) , (B) 9.6% (24) , and( AB) 8.4% (21) For the donors healthy control, ABO blood groups percentage were as follow: type (O) 36 % (108) type (A) 29.4% (88), type (B) 20.6% (62), and type (AB) 14% (42). The distribution of blood group among the patients with breast cancer and the donors from normal population that the result is highly significant (p<0.000). Conclusions: The study shows a strong correlation between the ABO group type and breast cancer and the highest frequency and percentage of patients with breast cancer was in blood group type (A).